The intervention effect of Amygdalus mongolica oil on the metabolomics and intestinal flora in pulmonary fibrosis - Li, Qian; Zhou, Hong-Bing; Liu, Jia-Qi; Bai, Wan-Fu; Wang, Jia; Yang, Zhan-Jun; Qiu, Min; Chang, Hong; Shi, Song-Li (Frontiers in Pharmacology, 2022)
Amygdalus mongolica oil is rich in unsaturated fatty acids such as inoleic acid (47.11%) and oleic acid (23.81%). Our research demonstrates that it exerts a protective effect on rat models of pulmonary fibrosis, however, little is known regarding the underlying mechanism of action. This study aimed to characterize the therapeutic mechanism of action of Amygdalus mongolica oil on bleomycin-induced pulmonary fibrosis in rats. Amygdalus mongolica oil appears to regulate the levels of potential key serum biomarkers which include Tetrahydrobiopterin, L-Serine, citrulline and Estradiol to participate in Folate biosynthesis, Glycine, serine and threonine metabolism, Arginine biosynthesis and Steroid hormone biosynthesis. And it also enriched intestinal microbial abundance, homogeneity and modulated the abundance of Duncaniell, Desulfovibrio, Peptococcaceae_unclassified, Dubosiella, Tyzzerella, Lachnospiraceae_NK4A136_group, Lactobacillus, Clostridiales_unclassified to exert a protective effect against pulmonary fibrosis. Amygdalus mongolica oil appears to confer protective effects against pulmonary fibrosis by affecting the level of pulmonary fibrosis metabolites and the abundance of related intestinal flora through multiple targets, as evidenced by our untargeted LC-MS/MS metabonomics evaluation and 16S rDNA sequencing technology.